The Relationship between Bullying Victimization and Academic Achievement among Adolescents in Malang - Dewi, Sagung Manik Dwi Purnama; Windarwati, Heni Dwi; Merdikawati, Ayut; Petriano, Haris (Universitas STRADA Indonesia, 2026)
Background: Adolescents who experience bullying may face various psychological and social consequences that can potentially affect their learning process at school. Being a victim of bullying may lead to fear, discomfort, and decreased learning motivation, which may ultimately influence students' academic achievement. Purpose: This study aimed to examine the relationship between bullying victimization and students’ academic achievement. Methods: The study was conducted in 2019 at SMP Negeri 5 Kepanjen, East Java, Indonesia. This study employed a cross-sectional design with a total sample of 283 respondents selected using purposive sampling based on predetermined criteria. The bullying victim instrument used in this study is a modified version of the Revised Cyber ​​​​Bullying Inventory (RCBI) and the Adolescent Peer Relations Instrument (APRI) to measure bullying victimization and the midterm examination scores to assess students’ academic achievement. Descriptive analysis was conducted to describe the characteristics of bullying victimization and students’ academic achievement, while the correlation analysis was performed using Spearman Rank. Results: The results showed that most respondents experienced low levels of bullying victimization with moderate academic achievement, accounting for 99 respondents (34.9%). The Spearman Rank correlation test indicated a statistically significant but weak negative correlation between bullying victimization and academic achievement (r = −0.174, p = 0.003), indicating that higher exposure to bullying is associated with slightly lower academic performance. Conclusion: The findings indicate that bullying victimization is associated with students’ academic achievement. Therefore, schools are expected to strengthen supervision, create a safe and supportive learning environment, and provide assistance for students who experience bullying in order to minimize its negative impact on the learning process.